In situ measurements of particle load and transport in dust devils - Metzger, S.; Balme, M.; Towner, Martin; Bos, B.; Ringrose, T.; Patel, M. (Academic Press, 2011)
In situ (mobile) sampling of 33 natural dust devil vortices reveals very high total suspended particle (TSP) mean values of 296 mg m−3 and fine dust loadings (PM10) mean values ranging from 15.1 to 43.8 mg m−3 (milligrams per cubic meter). Concurrent three-dimensional wind profiles show mean tangential rotation of 12.3 m s−1 and vertical uplift of 2.7 m s−1 driving mean vertical TSP flux of 1689 mg m−3 s−1 and fine particle flux of ~1.0 to ~50 mg m−3 s−1. Peak PM10 dust loading and flux within the dust column are three times greater than mean values, suggesting previous estimates of dust devil flux might be too high. We find that deflation rates caused by dust devil erosion are ~2.5–50 μm per year in dust devil active zones on Earth. Similar values are expected for Mars, and may be more significant there where competing erosional mechanisms are less likely.